Solution-processed TiO2/BiVO4/SnO2 triple-layer photoanode with enhanced photoelectrochemical performance - Hwang, Sung Won; Kim, Jin Un; Baek, Ji Hyun; Kalanur, Shankara S.; Jung, Hyun Suk; Seo, Hyungtak; Cho, In Sun (Journal of Alloys and Compounds, 2019)
The design of heterostructured multilayer oxide films for photoanodes enables the control of interfacial, charge transport/transfer and optical properties as well as stability, thus resulting in efficient photoelectrochemical (PEC) water splitting. Here, we report a triple-layered TiO2/BiVO4/SnO2 (T/B/S) photoanode that shows improved PEC water-oxidation performance and high visible transmittance at the wavelengths above 510 nm. The T/B/S photoanode was fabricated by a solution spin-coating method via a sequential deposition of the three layers. First, a bottom SnO2 layer with thickness ∼200 nm was deposited on a F:SnO2 (FTO) substrate. Subsequently, a BiVO4 middle layer (∼130 nm) and a TiO2 nanoparticle top layer (∼100 nm) were deposited. The three distinct layers of TiO2, BiVO4, and SnO2 deposited on the FTO substrates were free of voids and cracks. Importantly, the bottom SnO2 layer caused an increase in the lateral grain size (up to ∼600 nm) of the BiVO4 layer and formed a type-II heterojunction with the layer (similar to the BiVO4/WO3 case), thus efficiently improving charge separation and electron transport properties. Furthermore, the top TiO2 (anatase phase) layer formed a staggered conduction band structure with the BiVO4 layer and also protected the underlying layers against photocorrosion. The resultant T/B/S photoanode, which was devoid of any electrocatalyst, showed a higher photocurrent density of ∼2.3 mA/cm2 and ∼3.7 mA/cm2 at 1.23 V versus reversible hydrogen electrode for water oxidation and H2O2 oxidation, respectively, and a higher stability compared to those of BiVO4/SnO2 and pristine BiVO4 photoanodes.
Keywords: BiVO4/SnO2; Photoelectrochemical performance; Reversible hydrogen electrodes; Sequential deposition; Sol-gel spin coating; TiO2 overlayer; Type II hetero junctions; Visible transmittance; BiVO4/SnO2; Heterostructure; Photocurrent stability; Photoelectrochemical performance; Sol-gel spin-coating; TiO2 overlayer